Mangroves as Carbon Sequesterers: Diversity and Carbon Estimation Study in Pantai Mekar Village, Muara Gembong District, Bekasi Regency - Amin, Septian Faris Al; Pangestu, Agung Yoga; Dharma, Yossi; Sari, Nurika Arum; Maulidia, Oktarina; Octaviani, Eti Artiningsih; Anita, Vilda Puji Dini; Hasibuan, Mhd Muhajir; Dimyati, Ahmad Iqbal Wahid; Rahmasari, Shinta Nur; Agus, Ferri; Salimah, Wardah (Jurnal Biologi Tropis, 2025)
Mangrove forests are important for storing carbon dioxide (CO2) and reducing the effects of climate change. Indonesia possesses 20% of the global mangrove cover, which substantially impacts global climate mitigation efforts. However, understanding of the diversity of plant species in mangrove forests remains limited, as evidenced by the high rate of conversion of mangrove areas into aquaculture ponds, resulting in mangrove degradation. Our research in Pantai Mekar Village was conducted to augment information on mangrove plant species diversity in Indonesia, specifically in Bekasi Regency. Mangrove vegetation data were collected in Pantai Mekar Village, Muara Gembong, Bekasi from 8 to 12 July 2019. Data were collected using 2x2 m (seedlings and understory), 5x5 m (saplings), and 10x10 m (trees) plots. Importance value index (INP), Shannon-Wiener species diversity, evenness, richness, and carbon stock estimation were utilized to analyze the data. The study documented 21 species from 15 families. Species from the Acanthaceae family were predominant in the study site. Avicennia alba was the species with the largest biomass and carbon content. The estimated biomass contained in Mekar Beach is 380.42 tonnes/Ha with carbon sequestration of 190.21/Ha.